Description of Four- and Five-Nucleon Systems by Solving Faddeev-Yakubovsky Equations in Configuration Space - Lazauskas, Rimantas; Carbonell, Jaume (Frontiers in Physics, 2020)
Description of four- and five-nucleon systems by solving Faddeev-Yakubovsky equations in configuration space